Incidence and management of diarrhea in patients with HER2-positive breast cancer treated with pertuzumab - Swain, Sandra M.; Schneeweiss, Andreas (Annals of oncology, 2017)
Background. Pertuzumab disrupts heterodimerization between human epidermal growth factor receptor 2 (HER2) and epidermal growth factor receptor (EGFR), HER3, a